KORXONALAR FAOLIYATIDA EKOLOGIK INNOVATSIYALARNING IQTISODIY SAMARASI - Xalimov Shoxjaxon Xakimjon o‘g‘li (TADQIQOTLAR, 2026)
ABSTRACT This article analyzes the economic effects of implementing environmental innovations in enterprise activities. The study examines the impact of eco-innovations on production costs, resource efficiency, and financial performance of enterprises. The findings indicate that environmental innovations may require additional investments in the short term; however, in the long run they contribute to cost reduction and economic sustainability. Moreover, eco-innovations enhance enterprise competitiveness and reduce environmental risks. The article substantiates the importance of a gradual and strategic implementation of environmental innovations in business activities.